2018
DOI: 10.13044/j.sdewes.d5.0180
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Jet Fan Ventilation System installed in an Underground Car Park with Partition Walls

Abstract: The jet fan ventilation system is one of various ventilation systems available for the purpose of carbon monoxide extraction in underground car parks. Such a system is dependent not only on the rules applied during the design, but also the architecture of the underground car park. This paper describes a numerical model used to analyse air stagnation areas, airflow and streamline patterns and the influence of partition walls on the jet fan ventilation system. Additional focus is on the validity of the choice of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Air velocity profiles for Case Study-1, 2 and 3 are shown in Figure 4. In study of Ž. Špiljar et al [3], partition walls have been found to cause air stagnation. In our study also, cars that are identified as obstacle in CFD, caused to air stagnation where they located.…”
Section: Daily Ventilation Simulation Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Air velocity profiles for Case Study-1, 2 and 3 are shown in Figure 4. In study of Ž. Špiljar et al [3], partition walls have been found to cause air stagnation. In our study also, cars that are identified as obstacle in CFD, caused to air stagnation where they located.…”
Section: Daily Ventilation Simulation Resultsmentioning
confidence: 97%
“…The results show that the jet fan system not only prevents smoke spreading, but also provides good visibility to fire fighters when compared to the ducted ventilation system. Z. Spiljar et al [3] examined effect of partition walls of parking garage on the jet fan system. According to the results jet fan system is not suitable for all parking garages that especially includes partition walls.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of emergency scenario can improve visibility but may increase the average pollutant (i.e., CO 2 ) concentration. Špiljar et al 11 showed that increasing the number of jet fans does not improve the mechanical ventilation system efficiency. The selection of the number of jet fans, the distance between them, and the power of the extraction fans should be simulated by computational fluid dynamic software.…”
Section: Introductionmentioning
confidence: 99%
“…The jet fan ventilation system has been developed to ventilate the underground car parks for carbon monoxide (CO) removal during the normal condition as well as smoke extraction in the emergency scenario such as fire [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%